The Effect of Finger Painting Towards the Ability of Beginning Writing for Mild Intellectual Disability Students - Dyah Ayu Sawitri; M Shodiq; Agung Kurniawan (Department of Special Education, 2019)
Students with intellectual disability have obstacles in motoric maturity. Finger painting is used to prepare motoric maturity for beginning writing. This research describe: (1) pre-intervention of writing skill, (2) beginning writing skills after intervention, (3) effect of finger. Experimental research with Wilcoxon test. The result is that there is effect of finger painting. The calculation is obtained by Tcount= 0, α= 0,05, n=6, Ttable= 2. Ho is rejected and Hi is accepted because Tcount (0) ≤ Ttable. (4) The conclusion is that the average value of pre-test is 39 and the average post-test is 73. Thus, there are effect of finger painting towards the ability of the beginning writing of the students with intellectual disability.